2021
DOI: 10.1016/j.braindev.2021.02.007
|View full text |Cite
|
Sign up to set email alerts
|

High-dose pyridoxine treatment for inherited glycosylphosphatidylinositol deficiency

Abstract: Objective: We aimed to assess the efficacy and safety of high-dose pyridoxine treatment for seizures and its effects on development in patients with inherited glycosylphosphatidylinositol deficiencies (IGDs).Methods:In this prospective open-label multicenter pilot study, we enrolled patients diagnosed with IGDs using flow cytometry and/or genetic tests. The patients received oral pyridoxine (20-30 mg/kg/day) for 1 year, in addition to previous treatment.Results: All nine enrolled patients (mean age: 66.3 ± 44.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…These studies also did not address whether other ASMs were added or changed alongside with pyridoxine treatment. Recently, a prospective study showed the efficacy and safety of pyridoxine in nine individuals 15 . Unfortunately, only 4 out of 9 individuals were genetically proven to have inherited GPI deficiency ( PIGL and PIGO ) 15 and it was unclear to what extent existing ASMs were altered during each study to document a reduced seizure burden and how seizure burden was monitored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies also did not address whether other ASMs were added or changed alongside with pyridoxine treatment. Recently, a prospective study showed the efficacy and safety of pyridoxine in nine individuals 15 . Unfortunately, only 4 out of 9 individuals were genetically proven to have inherited GPI deficiency ( PIGL and PIGO ) 15 and it was unclear to what extent existing ASMs were altered during each study to document a reduced seizure burden and how seizure burden was monitored.…”
Section: Discussionmentioning
confidence: 99%
“…In neurons, pyridoxal is converted back to P5P and acts as a cofactor in the production of the inhibitory neurotransmitter γ‐aminobutyric acid 14 . In inherited GPI deficiency, there may be reduced neuronal TNSALP expression, which may in turn lead to intracellular P5P and γ‐aminobutyric acid deficiency 15 . This is the case in TNSALP‐deficient mice 16 and may underlie the intractable seizures observed in individuals with GPI anchoring disorders 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Although TNSALP is not the only GPI‐anchored protein that leads to seizures in GPI‐anchoring disorders, 46 it is, at least in theory, possible that treatment with vitamin B6 could counteract the reduced availability of TNSALP in neurons of patients with GPI‐anchoring disorders to reduce seizures 41,47 . The beneficial effect of pyridoxine treatment has been documented in seven patients with a genetically proven GPI‐anchoring disorder; however, none had PIGN encephalopathy 43,48–50 . Four patients were prospectively treated with 20–30 mg/kg/day for 1 year, 50 and the remaining patients were reported in retrospective case reports 43,48,49 .…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effect of pyridoxine treatment has been documented in seven patients with a genetically proven GPI‐anchoring disorder; however, none had PIGN encephalopathy 43,48–50 . Four patients were prospectively treated with 20–30 mg/kg/day for 1 year, 50 and the remaining patients were reported in retrospective case reports 43,48,49 . In PIGN encephalopathy, four previously reported patients and eight of our 10 patients who were treated with pyridoxine did not derive any benefit in terms of seizure reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation with vitamin B6 to bypass the requirement for membrane-bound alkaline phosphatase and sodium benzoate to increase the transcription of PIGM have been partially helpful in some patients. [3][4][5][6] In 1980, at their Montreal congress, the International Society of Blood Transfusion established a working party for blood group terminology. 7 As of February 2021, they have identified 43 blood group systems.…”
mentioning
confidence: 99%